Sintering effects on mechanical properties of glass-reinforced hydroxyapatite composites - (:unkn) unknown (ELSEVIER SCI LTD, 2002)
The improvement of mechanical properties or hydroxyapatite (HA) with reinforcement of two (45.5 wt.% P2O5. 54.5 wt.% CaO) and three-oxide (45 wt.% P2O5 28 wt.% CaO, 27 wt.% Na2O) glasses with different sintering temperatures is studied. Although HA shows great biocompatibility with the human body, its applications are limited to non load-bearing areas and coatings due to its low mechanical properties, These mechanical properties can be improved substantially with addition of glass ceramics by sintering. In this study, naturally produced HA from human teeth is sintered with varying addition of two and three-oxide glass ceramics, The microhardness measurements, the density and the compression tests are performed in order to find the optimum sintering temperature. Finally average hardness value of 285+/-19 HV. average density of 2.79+/-0.05 g cm(-3) and compressive strength value of sigma(avr)=67+/-17 MPa have been achieved by sintering at 1200degreesC with the addition of 10 wt.% two oxide glass into the HA. Results are implying that 10 wt.% of glass addition for HA composites is the maximum limit for such composites. Observations are supporting the idea that sodium free glasses could be better conciliated with the HA structure at high temperatures. (C) 2002 Elsevier Science Ltd and Techna S.r.l. All rights reserved.
Keywords: A. sintering; B. composites; D. glass ceramics; hydroxyapatite; PHOSPHATE; CERAMICS